Color Visualization of the Artistic Image as a Feature of G. R. Derzhavin’s Creative Method - K. A. Potashova (Научный диалог, 2019)
The relevance of the problem is associated with the need to clarify the features of the creative method of G. R. Derzhavin. The novelty of the study is in the presentation of the colouristic polyphonism of Derzhavin’s poetics as a means of visualizing an artistic image. The article discusses the peculiarities of colour and black-and-white solutions of verbal portraits and landscapes in Derzhavin’s poetry, defines the technique for attracting pictorial elements into the poetics of the text, outlines a peculiar manner of Derzhavin’s vision related to the perception of the contemplated world as a picture. It is shown that Derzhavin, following his poetic doctrine that “poetry is speaking painting”, brings to the literature the techniques of visual art: the principle of color contrast, the reconstruction of a light-air perspective, the observance of the chosen colour palette. The article identifies the mechanisms of verbal colour transmission. It is proved that Derzhavin’s colour is represented in an abundance of semantic shades transmitted through complex colouristic epithets. Conclusions are drawn that, perceiving wildlife as an aesthetic object, Derzhavin represents the enormity of the universe in an abundance of variously coloured minute details. It is argued that the colours in Derzhavin’s poetry constitute a matrix of meanings. The dominance of the poetics of colour objectivity in Derzhavin’s work allows us to talk about colour realism as the basis of the poet’s artistic method.